Perkembangan Literasi Keuangan Islam: Studi Bibliometrik - Nuraini, Azdina; Monoarfa, Hilda; Juliana, Juliana (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2024)
This study aims to analyze and map the development of literature on Islamic financial literacy. This study uses bibliometric method with VOSviewer and Microsoft Excel as the analysis tool. There were 84 relevant articles collected through the Scopus database obtained using the keyword